Duck & Goose - Hills, Tad. (New York : Schwartz & Wade Books, 2006)
Duck and Goose learn to work together to take care of a ball, which they think is an egg.
Ages 3-7.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Interpersonal relations -- Fiction; Ducks -- Fiction; Geese -- Fiction; Interpersonal relations -- Juvenile fiction; Ducks -- Juvenile fiction; Geese -- Juvenile fiction